Enhancing Students’ Reading Competence through Multilingual Texts in Modern Education - Urinova, Durdona Farhodovna (The Lingua Spectrum, 2026)
This article broadly examines the issue of developing students’ reading competence through the use of multilingual texts based on modern teaching methods from both theoretical and practical perspectives. The article provides a detailed analysis of the pedagogical, psychological, and linguistic significance of multilingual texts in the reading process and explains their role in enriching students’ vocabulary, improving deep text comprehension, and developing analytical and critical thinking skills. Furthermore, effective ways of using multilingual texts through digital learning environments, interactive technologies, and innovative teaching methods are highlighted. The article also emphasizes the importance of the multilingual approach in increasing students’ motivation, developing independent thinking, strengthening intercultural communicative competence, and enhancing interest in reading activities. In addition, it is scientifically justified that lessons organized through multilingual texts increase students’ classroom participation, improve reading speed and comprehension levels, and serve as an effective pedagogical tool in modern education. The results of the study confirm that reading activities conducted through multilingual texts significantly improve students’ reading efficiency and positively influence the development of reading competence.